FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PELAYANAN FISKUS, KONDISI KEUANGAN WAJIB PAJAK DAN PREFERENSI RISIKO TERHADAP KEPATUHAN WAJIB PAJAK (Studi Empiris Pada Wajib Pajak UMKM Di KPP Semarang Timur) - Moch Ali Munawar, 13.05.52.0216; Meita Oktaviani, Rachmawati (Students' Journal of Accounting and Banking, 2017)
This research aims to examine the the factors that affect the quality of service tax, taxpayer financial condition and risk preference to taxpayer compliance. The sampling method of this research used convenience sampling with a sample of 95 respondent from UMKM taxpayer’s in Semarang City. Is this research, data analysis, used by Multiple Regression Analysis. the results of this study indicate that the quality of fiscal services have a significant effect on taxpayer compliance UMKM,while the financial condition of taxpayers and risk preferences have no significant effect on taxpayer compliance UMKM.Keywords: Tax Service Quality, Financial Condition of Taxpayer’s, Risk Preference, and Taxpayer’s Compliance